Security assessment via vulnerability assessment: Case of the CCS-TSG of DLSU Manila - EgbeAyuk, Orock (Animo Repository, 2022)
With cybercrimes on the increase, cybersecurity has become vital nowadays. Companies worry regarding attacks like breaches, however, a few have put in place systems to protect against these attacks. It has become impossible to manually review network systems for security flaws. The most effective technique to this point to check the effectiveness of those security measures is by conducting a Vulnerability Assessment and subsequent penetration testing. A vulnerability is any programming error or misconfiguration that could allow an intruder to gain unauthorized access to a system. The main aim of carrying out vulnerability assessment is to spot and report vulnerabilities. The test is carried out to verify that networks and systems don't seem to be susceptible to a security risk that would enable unauthorized access to resources. This analysis provides a summary of a vulnerability assessment carried out by the College of Computer Sciences- Technical Services Group (CCS-TSG) of De La Salle University-Manila. This department of the College of Computer Studies is responsible for carrying out maintenance, installation, and configuration of services. It is a newly created department and this work summarizes the first vulnerability assessment carried out on the system. The CCS-TSG set up machines on the cloud for users, which would make it prone to security issues. In this work we shall carry out a vulnerability assessment with the help of automated tools, generate a report and provide documentation that will serve as a reference to future assessments on the system. Keywords: Cybersecurity, Cybercrimes, breaches, Information Security, Vulnerabilities, Vulnerability Assessment, Penetration Testing.